2011
DOI: 10.1093/jnci/djr243
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Pancreatic Cancer Chemoresistance by Inhibition of TAK1

Abstract: The results of this study suggest that genetic silencing or inhibition of TAK1 kinase activity in vivo is a potential therapeutic approach to reversal of the intrinsic chemoresistance of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 47 publications
4
131
0
1
Order By: Relevance
“…We next sought to identify proteins selectively thiophosphorylated by AS-TAK1 f in lysates from four cell lines from two cancer types, colorectal (CaCo2, SW620) and pancreatic (PC3, DU145). These cell lines were selected because TAK1 has been shown to be particularly important in colorectal and prostate cancers (18,19). Lysates were individually labeled by spiking in N 6 -furfuryl-ATPγS and purified AS-TAK1 f , WT-TAK1 f , or with no added kinase.…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to identify proteins selectively thiophosphorylated by AS-TAK1 f in lysates from four cell lines from two cancer types, colorectal (CaCo2, SW620) and pancreatic (PC3, DU145). These cell lines were selected because TAK1 has been shown to be particularly important in colorectal and prostate cancers (18,19). Lysates were individually labeled by spiking in N 6 -furfuryl-ATPγS and purified AS-TAK1 f , WT-TAK1 f , or with no added kinase.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CXCR4 signaling regulated by NF-kB has also been reported serving as a counter defense mechanism against gemcitabine in PDAC (10), which is most like another parallel pathway regulated by NF-kB. Our previous studies showed that PDAC cells with silenced TAK1 had lower NF-kB activity and were more sensitive to gemcitabine, suggesting that activation of NF-kB played an important role in chemoresistance (20).…”
Section: Discussionmentioning
confidence: 95%
“…All mice were weighed every 5 days and observed for tumor growth. Bioluminescence imaging of tumors was conducted using a cryogenically cooled IVIS 100 imaging system as previously described (20). The day after the end of treatment, the mice were euthanized by carbon dioxide inhalation and the tumors were excised and weighed.…”
Section: Animal Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, overexpression of TAK1 could promote the tumor growth and metastatic capacity of ovarian cancer cells by enhancing NF-kB transactivity (11). However, deletion of the TAK1 gene in skin tumors induces tumor cell apoptosis, and inhibition of TAK1 kinase activity leads to a proapoptotic phenotype and reverts the intrinsic chemoresistance of pancreatic cancer (12,13), suggesting that targeting TAK1 might be a promising and effective therapeutic approach to counteract tumor progression. In addition, TAB3, the key factor of the TAK1/TAB2/3 complex, is markedly elevated in a variety of cancers (14), and silencing either TAK1 or TAB3 could enhance the rates of doxorubicin-induced apoptosis and the chemosensitivity of hepatocellular carcinoma cells (15).…”
Section: Introductionmentioning
confidence: 99%